POGŁOSKI O SPRAWIE TEMPLARIUSZY - PRZEPŁYW INFORMACJI W SPOŁECZEŃSTW ACH EUROPY ZACHODNIEJ NA POCZĄTKU XIV WIEKU - Satora, Magdalena (In Gremium. Studies in History, Culture and Politics, 2011)
THE RUMORS ABOUT THE TEMPLAR CASE - THE FLOW OF INFORMATION IN WESTERN EUROPE SOCIETIES AT THE BEGINNING OF THE 14TH CENTURY The sudden arrests of the French Templars in October 1307 was a great surprise both to the most important participants of the political life of Western Europe and to the members of the order, which had played an important role in the courts of particular countries of this part of the continent and the papal curia for over two hundred years. Since the actions against their community did not start at the same time in the whole of the Christian world, the Templar’s that weren’t staying in France had had the time to prepare for the expected attack.